Decreasing Biological Production and Carbon Export Due to the Barrier Layer: A Case Study in the Bay of Bengal - Zhang, Huangchen; Zhou, Linbin; Li, Kaizhi; Ke, Zhixin; Tan, Yehui (Frontiers in Marine Science, 2021)
A freshwater-induced barrier layer (BL) is a common physical phenomenon both in coastal waters and the open ocean. To examine the effects of BL on the biological production and the associated carbon export, a physical-biogeochemical survey was conducted in the Bay of Bengal. Severe depletions of surface phosphorus and the deepening of the nutricline were observed at the BL-affected stations due to the vertical mixing prohibition. The lowered surface chlorophyll a (Chl a) and squeezed deep Chl a maximum (DCM) layer also resulted in the ~18% lowered vertically integrated Chl a at the said stations. The composition of the net-sampled zooplankton was altered, and the abundance decreased by half at the BL-affected station (29.68 ind. m−3) compared with the unaffected station (55.52 ind. m−3). Such reductions in major zooplankton groups were confirmed by a video plankton recorder (VPR). The VPR observation indicated that there was a lower (by one-half) abundance of detritus at the BL-affected station, while the much lower carbon export flux rates were estimated to be at the BL-affected station (0.31 mg C m−2 d−1) rather than the unaffected station (0.77 mg C m−2 d−1). An idealized one-dimensional nutrient-phytoplankton-detritus model identified that the existence of BL can lead to decreased surface nutrients and phytoplankton concentrations, squeezed DCM layers, and lower detritus abundances. Finally, this study indicated that BL layers inhibit biological production and reduce carbon export, thus playing an important role in the ocean biogeochemical cycles.